2022
DOI: 10.1007/s10753-022-01633-0
|View full text |Cite
|
Sign up to set email alerts
|

Polyene Phosphatidylcholine Interacting with TLR-2 Prevents the Synovial Inflammation via Inactivation of MAPK and NF-κB Pathways

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune joint disease that causes cartilage and bone damage or even disability, seriously endangering human health. Chronic synovial in ammation has been shown to play a vital role in the disease sustainability. Therefore, down-regulation of synovial in ammation is considered to be an effective discipline for RA therapy. Polyene phosphatidylcholine (PPC) is a hepatoprotective agent, which was observed to inhibit in ammation in macrophages and prevent collagen-induced a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Xu et al revealed that Polyene Phosphatidylcholine prevented synovial inflammation via inactivation of NF-κB signaling. 38 Ma et al demonstrated that NF-κBp65 was involved in the mechanism of Jinzhen on novel SARS-Cov-2. 39 Yang et al demonstrated that the NF-κB pathway was related to Thioredoxin-1 mediates neuroprotection of Schisanhenol in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al revealed that Polyene Phosphatidylcholine prevented synovial inflammation via inactivation of NF-κB signaling. 38 Ma et al demonstrated that NF-κBp65 was involved in the mechanism of Jinzhen on novel SARS-Cov-2. 39 Yang et al demonstrated that the NF-κB pathway was related to Thioredoxin-1 mediates neuroprotection of Schisanhenol in SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that the NF‐κB signal pathway plays a critical role in human disease. Xu et al revealed that Polyene Phosphatidylcholine prevented synovial inflammation via inactivation of NF‐κB signaling 38 . Ma et al demonstrated that NF‐κBp65 was involved in the mechanism of Jinzhen on novel SARS‐Cov‐2 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Astragaloside IV, Xiang Lin pills, berberine, and fluoxetine can inhibit the TLR4/MyD88/NF-κB signals, thereby exerting the effects of acute myocardial infarction, colitis, and ischemia-reperfusion injury, and relieve postoperative cognitive dysfunction and neuroinflammation in elderly mice [67][68][69][70][71][72][73][74][75][76][77][78][79][80]. Polyene phosphatidylcholine, a wellknown hepatoprotective drug, has also recently been found to act on the TLR2/MyD88 signaling pathway, inhibiting the binding of MyD88 and TLR, and activating the IκB kinase (IKK) complex to alleviate synovial inflammation [81]. In addition, studies have reported that pioglitazone can reduce oxidative stress through the TLR4/MyD88/NF-κB signaling pathway, thereby ameliorating the testicular toxic side effects of cisplatin treatment [75].…”
Section: Drug Therapy Targeting Myd88mentioning
confidence: 99%
“…This thus inhibits M1 and promotes M2 activation in macrophages. Additionally, the interaction between PPC and TLR-2 can suppress the release of pro-inflammatory cytokines (TNF-a, IL-6) and promote the production of anti-inflammatory cytokines (IL-10, TGF-β) in macrophages, thereby promoting macrophage polarization toward M2 and alleviating the symptoms of rheumatoid arthritis (Pan et al 2017 ; Xu et al 2022b ). Considering that LN is an immune-related disease similar to rheumatoid arthritis, PPC may be potentially used for the future treatment of LN.…”
Section: Targeting Metabolic Reprogramming To Regulate Macrophage Pol...mentioning
confidence: 99%